Amélioration de la qualité des carcasses et des viandes - BONNEAU, M.; TOURAILLE, C.; PARDON, P.; LEBAS, F.; FAUCONNEAU, B.; REMIGNON, H. (INRAE Productions Animales, 1996)
pas de résumé disponible pour cet article